Pengaruh Keamanan dan Kepercayaan terhadap Repurchase Intention (Studi Kasus pada Shopee di Jakarta Barat) - Iwan, Iwan; Purwatiningsih, Purwatiningsih (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2023)
The development of information and communication technology brings very fast changes at this time, many people use the internet for buying and selling transactions. The purpose of this study is to determine the effect of security and trust on repurchase intention at e-commerce Shopee, partially or collectively. The method used in this research is regression. By using the independent variables of security and trust while the dependent variable uses repurchase intention. This study used a sample of 155 people from a student population who had shopped online at Shopee in the West Jakarta area. As for the results, trust has a positive and significant effect on repurchase intention, while security has no effect on repurchase intention. simultaneously (together) security and trust have a significant effect on Repurchase Intention. Keywords: Security, Trust, Purchase Intention